Attitudes and Social Influence in Sustainable Fashion: Rethinking the Role of Corporate Initiatives among College Students in Taiwan - Sulistyandari, Sulistyandari; Aryoko, Yudhistira Pradhipta; Tampubolon, Sabarmuddin (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2025)
The growing demand for sustainability in the fashion industry has encouraged corporations to invest significantly in Corporate Social Responsibility initiatives. Yet, it remains unclear whether these efforts truly influence consumer behavior. This study explores how corporate, psychological, and social factors shape sustainable fashion consumption among college students in Taiwan. Grounded in the Theory of Planned Behavior, the Value-Belief-Norm Theory, and Social Influence Theory, the research examines five key predictors: Attitudes Toward Sustainability, Social Norms, Environmental Knowledge, Perceived Economic Constraints, and Corporate Social Responsibility initiatives. Empirical data were gathered from 250 university students and subjected to examination utilizing Partial Least Squares Structural Equation Modeling. Research indicates that an individual’s personal beliefs and cultural expectations significantly influence their likelihood of purchasing environmentally-conscious clothing. In contrast, environmental knowledge, economic constraints, and Corporate Social Responsibility initiatives have no significant impact. Individual beliefs and societal norms appear to have a more significant influence on environmentally conscious purchasing decisions than data-driven or financial considerations. The minimal impact of corporate ethical programs reveals that simply implementing sustainability strategies from the top down is unlikely to transform consumer choices without genuine community involvement and widespread social approval. Overall, this study contributes to the literature on sustainability and consumer behavior by emphasizing a consumer-centered approach. It highlights that moral conviction and peer influence are more effective in promoting sustainable fashion consumption than corporate messaging. Practical insights are also provided for marketers and policymakers to encourage genuine behavioral transformation toward sustainability in the fashion sector.